1997
DOI: 10.1021/jp9722465
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Composition of Mixed Hydrogenated and Fluorinated Micelles by Small Angle Neutron Scattering

Abstract: The compositions of mixed micelles formed in aqueous solutions of sodium dodecanoate and sodium perfluorooctanoate at different total surfactant concentrations and at three (0.33, 0.53, and 0.73) sodium perfluorooctanoate mole fractions were determined by the small angle neutron scattering technique coupled with the external contrast method. At each concentration, measurements were performed as functions of the solvent H2O/D2O composition in order to determine the micellar neutron scattering densities. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…In the present study, we have used c = 45mNm 21 . Similarly, eqn ( 11)- (13) give the strength and nature of interaction among the components at the interface as well as the activity coefficients of the two components…”
Section: Surface Tension Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have used c = 45mNm 21 . Similarly, eqn ( 11)- (13) give the strength and nature of interaction among the components at the interface as well as the activity coefficients of the two components…”
Section: Surface Tension Datamentioning
confidence: 99%
“…Different combinations of surfactant systems, like cationic/cationic, cationic/anionic, cationic/nonionic, anionic/anionic, anionic/nonionic and nonionic/nonionic have been studied using a wide array of different experimental techniques, like electron spin resonance, fluorescence quenching, Guoy interferometry, surface tensiometry, neutron X-ray scattering, PGSE-NMR, static/ dynamic light scattering, etc. [10][11][12][13][14][15][16][17][18] Among these, ionic/nonionic systems are more important as they exhibit highly nonideal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…2 This is due to the difficulty in finding experimental methods able to discriminate between the contributions of the different surfactants to the observed property, and, at the same time, to elaborate theoretical treatments representative of the mixed aggregation process. Various papers have been published reporting and discussing experimental studies on surfactant mixtures, using electron spin resonance, 3 static and dynamic light scattering, 4 neutron scattering, 5,6 fluorescence quenching, 7 Gouy interferometry, 8 and surface tension. [9][10][11] The pulsed gradient spin echo (PGSE)-NMR technique, which was firstly applied to this kind of system by Carlfors and Stilbs, 12 was found to be one of the most informative.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic 7 and structural 20 studies proved that NaL and NaPFO are miscible with each other leading to the formation of mixed micelles the composition of which is a function of m t and X NaPFO . In particular, small angle neutron scattering measurements 20 demonstrated that the micellar composition monotonically increases and decreases with m t for X NaPFO ¼ 0.33 and 0.73, respectively, tending to the stoichiometric value at high concentration whereas it is independent of m t for X NaPFO ¼ 0.53. On this basis, one expects contributions to the apparent molar properties for the change of the micellar composition specific of the NaL/NaPFO ratio.…”
Section: Quantitative Analysis Of the Thermodynamic Propertiesmentioning
confidence: 99%